Discovery Teaching about Calculating Side Lengths of Right Triangles Using Pythagoras Theorem with the Help of Geogebra Software - Nguyen, Ngoc-Giang (Advances in Social Sciences Research Journal, 2021)
Discovery teaching is an active teaching method that encourages learners to create their own knowledge. Students who participate in the discovery learning process will remember longer than the conventional teaching method. This teaching method is very important in the process of teaching innovation in Vietnam when changing from a teaching method that focuses on knowledge transmission to one that focuses on developing learners’ capacity. Our study proposes an exploratory teaching method for calculating the side lengths of right triangles using the Pythagoras theorem with the help of GeoGebra software. By the method of empirical investigation, we surveyed 51 students in Bien Hoa city and used descriptive statistics with the help of SPSS software, the research has shown that the discovery teaching of calculating side lengths of right triangles using Pythagoras theorem with the help of GeoGebra software is needed. However, many teachers still do not fully understand the discovery teaching method. The research results also show that there are three groups of factors affecting the way of discovery teaching. First, the effort of teachers in teaching discovery is huge. Second, the time spent on discovery teaching is relatively large. Third, the current teaching environment has not yet met the requirements of discovery teaching. The findings from the research results are important for proposing a way of discovery teaching about calculating the side lengths of right triangles using Pythagoras theorem with the help of GeoGebra software.